Effect of Polymer Concentration on the Photocatalytic Membrane Performance of PAN/TiO2/CNT Nanofiber for Methylene Blue Removal through Cross-Flow Membrane Reactor - Lathifah Puji Hastuti; Ahmad Kusumaatmaja; Adi Darmawan; Indriana Kartini (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
A photocatalytic membrane combining photocatalyst and membrane technology based on polyacrylonitrile (PAN) and TiO2/CNT has been developed. Such combination is to overcome fouling formation on the membrane, thus prolonging the membrane lifetime and enhancing the efficiency on the waste treatment. PAN nanofiber was prepared by electrospinning method. The precursor solution was dissolved PAN and dispersed TiO2/CNT in N,N-Dimethylformamide (DMF). PAN concentration in the precursor solution was varied at 4.5, 5.5, 6.5, 7.5, and 8.5%. The effect of PAN concentration on the fiber morphology and pore size was discussed. The performance of the resulted membrane on methylene blue (MB) removal was also investigated on a cross-flow system. SEM images of the resulted membrane identified that PAN nanofiber was successfully fabricated with random orientation. The PAN 6.5% showed the highest diffraction intensity of the anatase crystalline phase of TiO2. The additions of CNT and TiO2 lead to the formation of a cluster of beads as confirmed by TEM. Increasing the concentration of PAN increased the fiber diameter from 206 to 506 nm, slightly decreased the surface area and pore size, respectively, from 32.739 to 21.077 m2.g−1 and from 6.38 to 4.75 nm. The PAN/TiO2/CNT nanofibers show type IV of the adsorption-desorption N2 isotherms with the H1 hysteresis loops. Membrane PAN/TiO2/CNT at PAN concentration of 6.5% shows the optimum performance on the MB color removal by maintaining the percentage of rejection (%R) at 90% for 240 min and permeability of 750 LMH. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).